Horatio Gates Spofford correspondence - Spofford, Horatio Gates
ALS (1818 October 16) from Spofford to Harry Croswell describing his cabin in western Pennsylvania and the establishment of a settlement in Venango County; and ALS (1822 May 20) from Spofford to Stephen Van Rensselaer requesting information for his gazetteer of New York state.
Author, surveyor, civil engineer, and Quaker.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Croswell, Harry, -- 1778-1858 -- Correspondence; Van Rensselaer, Stephen, -- 1764-1839 -- Correspondence; Quakers; New York (State) -- Gazetteers; Pennsylvania -- History -- 1775-1865.; Venango County (Pa.) -- History; Authors; Civil engineers; Surveyors